Clinical characteristics and complications of skull base osteomyelitis: A 12-year study in a teaching hospital in South India - Das, Sohini (J Family Med Prim Care, 2019)
CONTEXT: Skull base osteomyelitis (SBO) is an uncommon disease with substantial morbidity and mortality. AIMS: The aim of this study is to characterize clinical features, outcomes, and complications of SBO. We also looked at differences in clinical profile in otogenic and non-otogenic SBO. MATERIALS AND METHODS: This is a single-center retrospective observational study. Patients aged more than 15 years of age with clinical and radiological diagnosis of SBO admitted in general medicine department in a teaching hospital in South India from March 2006 to February 2018 were recruited. RESULTS: A total of 41 patients with SBO were identified and included. Mean age was 56.9 ± 10.7 years. In all, 90% of patients (37/41) had diabetes mellitus and 29% (12/41) had recent head/neck surgery. Only 19% (8/41) needed ICU care, and mortality was 21% (9/41). Most common symptom was headache seen in 73% (30/41) of patients. Majority, 61% (25/41), had otogenic infections. Otogenic infections were associated with longer duration of diabetes mellitus (mean = 11.5 vs. 5 years, P = 0.01), higher creatinine levels (mean = 1.66 vs. 0.9 mg/dL, P = 0.014, odds ratio [OR] = 3.8), and higher incidence of cranial nerve palsy (92% vs. 56%; OR = 8.9) compared to non-otogenic SBO. Cranial nerve palsy (78%), meningitis (63%), and cerebral venous thrombosis (43%) were frequent complications of SBO in this study. The causative organisms for SBO in our cohort was bacterial in 60% (15/25) and fungal in 40% (10/25) of the patients. Surgical debridement for source control was done in 54% of patients (22/41) and was associated with survival at discharge (P = 0.001). CONCLUSIONS: Bacterial infections are the most common cause of SBO. Otogenic SBO is associated with longer duration of diabetes mellitus and higher incidence of cranial nerve palsy. Therapeutic surgical debridement plays an important role in treatment of SBO and is associated with improved survival.